Determinan keputusan pembelian MIXUE: Pendekatan fenomenologi - Putlia, Grace; Sundoro, Hary Saputra; Rajawen, Katedra Mentari (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The first aim of this research is to find out what factors influence MIXUE purchasing decisions in Tangerang. The second objective is to find out how these factors can influence MIXUE purchasing decisions in Tangerang. A total of 10 informants were obtained to conduct in-depth interviews. The collected data will be analyzed using Interpretative Phenomenological Analysis (IPA) with stages: (1) reading and re-reading, (2) initial noting, (3) developing emergent themes, (4) searching for connections across emergent themes, (5) moving the next cases, and (6) looking for patterns acros cases. The results of data processing state that the factors that influence purchasing decisions are advertisin3g, 4P, and lifestyle. Meanwhile, regarding how these factors can influence decisions, the factors are advertising, lifestyle and the 4Ps.